Risk Factors for the Incidence of Low Birth Weight Babies in Hospital TK IV 07.01 Lhoukseumawe - Nurliah Nurliah; Cut Linar; Murniati Murniati; Lina Ekawati; Rahmad Mouliansyah; Mawarni Yunita (International Journal Of Health Science, 2025)
Based on the data obtained, 157 babies were born with LBW in 2016. In 2017 there were 142 babies born with LBW. In 2018 there were 134 babies born with LBW. Based on the results of an initial survey conducted by researchers at the TK IV 07.01 Lhokseumawe Hospital, the prevalence of LBW every month is still high from the last 3 years. The purpose of this study was to analyse the risk factors for the incidence of low birth weight babies at the Hospital TK IV 07.01 Lhokseumawe in 2024. The design of this study was quantitative research with a retrospective approach. The population of this study was 138 people, the sample was obtained by saturated sampling technique as many as 138 people. Univariate analysis, bivariate using chi-square and multivariate using multiple logistic regression at 95% confidence level. The results showed that the variables that had a risk with the incidence of LBW in Hospital TK IV 07.01 Lhokseumawe in 2024 were multiple pregnancies (p=0.026 <0.05) and a history of premature birth (p=0.017 <0.05). Variables that did not have a risk with the incidence of LBW were maternal age (p=0.847 >0.05), preeclampsia/eclampsia (p=1.000 >0.05), pregnancy distance (p=0.0322 <0.05) and premature rupture of membranes (p=0.439 >0.05). The study concluded that the incidence of LBW was influenced by 2 factors, namely multiple pregnancies and a history of preterm birth. The most dominant factor influencing it is the history of premature pregnancy.